Acoustic emission study of fatigue crack propagation in Q345R - CHAI Meng-yu; DUAN Quan; ZHANG Zao-xiao (工程科学学报)
The acoustic emission signals of fatigue crack propagation in Q345R,which is the typical representative of common steel for pressure vessels,were investigated in detail to construct a relationship between fatigue and acoustic emission. The results show that there are three distinct stages of acoustic emission during fatigue crack propagation in Q345R. Cumulative count and cumulative energy can characterize the whole fatigue crack propagation well. The transition from the 2nd stage to the 3rd stage of acoustic emission advances that of linear elastic fracture mechanics,indicating that acoustic emission is more sensitive to the unstable fracture stage of fatigue crack propagation. The relations of count rate and energy rate to fatigue crack propagation rate of Q345R are established respectively for predicting the remaining life of Q345R.